Relationship between Customer\'s Perceptions on Cleanliness of Surfaces and the Method of Measuring Surface Pollution Using ATP (Illuminometer) in a Restaurant - Fathollah Gholami-Borujeni; Hadi NikNejad (Journal of Mazandaran University of Medical Sciences, 2022)
Relationship between Customer's Perceptions on Cleanliness of Surfaces and the Method of Measuring Surface Pollution Using ATP (Illuminometer) in a Restaurant